The Relevance of the Doctrines of Natural Law, Human Rights and International Law to the Principle of Self-Determination: The Case of Nigeria (Strathmore Law Journal, 2023)
In recent times, worldwide, agitations for self-determination, whether internal or external (secession), are becoming common.  Also, in Nigeria, the agitation for self-determination has become intense. Historically, multiple independent nationalities were cobbled together by the British to form the nation called “Nigeria” without first seeking and obtaining their consent. Invariably, Nigeria is often under threats of instability due to separatist agitations from her diverse ethnic groups. Although, self-determination is expressed to be a “right’’ in different international legal instruments like the United Nations Charter and the African Charter on Human and Peoples’ Rights (ACHPR) and even the International Court of Justice (ICJ) has declared it to be of erga omnes in nature, the nature of this “right’ is still controversial. For instance, it is argued that the right to self-determination originated from natural law. Separatists in Nigeria, agitating for self-determination anchor their arguments on this contention. This paper examine the agitations for self-determination in Nigeria from the standpoints of natural law, the doctrine of human rights and the principles of international law. The objectives are to know if self-determination originated from natural law, and to see the nexus between self-determination and the doctrine of human rights. Also, to identify the status of self-determination as a right under international law; and how all these apply to the Nigerian situation. The paper adopted doctrinal research methodology, using both primary and secondary sources. The paper concluded that the tripartite doctrines of natural law, human rights and international law apply to the Nigerian situation.